In situ fucosylation of the Wnt co-receptor LRP6 increases its endocytosis and reduces Wnt/β-catenin signaling - Hong, Senlian (Cell Chem Biol, 2020)
Wnt/β-catenin signaling regulates critical, context-dependent transcription in numerous physiological events. Amongst the well-documented mechanisms affecting Wnt/β-catenin activity, modification of N-glycans by L-fucose is the newest and the least understood. Using a combination of Chinese hamster ovary cell mutants with different fucosylation levels and cell-surface fucose editing (in situ fucosylation; ISF), we report that α(1–3)-fucosylation of N-acetylglucosamine (GlcNAc) in the Galβ(1–4)-GlcNAc sequences of complex N-glycans modulates Wnt/β-catenin activity by regulating the endocytosis of low density lipoprotein receptor-related protein 6 (LRP6). Pulse-chase experiments reveal that ISF elevates endocytosis of lipid-raft-localized LRP6, leading to the suppression of Wnt/β-catenin signaling. Remarkably, Wnt activity decreased by ISF is fully reversed by the exogenously added fucose. The combined data show that in situ cell-surface fucosylation can be exploited to regulate a specific signaling pathway via endocytosis promoted by a fucose binding protein, thereby linking glycosylation of a receptor with its intracellular signaling.